2015
DOI: 10.1159/000430373
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Inhibition of Focal Adhesion Kinase Attenuates Cardiac Fibrosis in Mice Cardiac Fibroblast and Post-Myocardial-Infarction Models

Abstract: Background: To investigate the role of focal adhesion kinase (FAK)-mediated signaling in hypoxia-induced cardiac fibroblasts (CFs) differentiation and cardiac fibrosis post-myocardial infarction (MI) on a mice model. Methods: CFs of neonatal C57BL/6 mice were treated under normoxic, hypoxic, or hypoxic+PP2 (known as a Src kinase family inhibitor) conditions. Gene expressions of FAK, alpha-smooth muscle actin (α-SMA) and collagen type I alpha 1 (Col1α1), or α-SMA and vimentin levels were performed by RT-PCR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 25 publications
(43 reference statements)
1
33
0
Order By: Relevance
“…Accumulating evidence has demonstrated that excessive fibrosis would lead to ventricular dilation, infarct expansion, and heart failure [9-11]. Thus, effective interventions to inhibit cardiac fibrosis may have potential therapeutic effects on improving heart function and even reducing mortality risk [12-14]. …”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that excessive fibrosis would lead to ventricular dilation, infarct expansion, and heart failure [9-11]. Thus, effective interventions to inhibit cardiac fibrosis may have potential therapeutic effects on improving heart function and even reducing mortality risk [12-14]. …”
Section: Introductionmentioning
confidence: 99%
“…We also showed that in contrast to LRP1 inhibition, PP2 expression did not alter vascular cell pro‐inflammatory phenotypes. PP2‐mediated Pyk2 phosphorylation inhibition has been shown to efficiently reverse fibrosis development in a load‐induced cardiac hypertrophy mouse model and to attenuate fibrosis after MI . Here, we showed for the first time the temporal and spatial evolution of pPyk2 levels after MI.…”
Section: Discussionmentioning
confidence: 63%
“…The MI model was characterized as previously described (Fan et al, 2015). Mice were anesthetized by intraperitoneal administration of tribromoethanol (400 mg/kg) and ventilated with a rodent respirator, then the left anterior descending coronary artery was permanently occluded using a 7-0 polypropylene suture, and the occlusion was confirmed by blanching of the anterior wall of the left ventricle.…”
Section: Methodsmentioning
confidence: 99%